Comparative transcriptomic analysis of the super hybrid rice Chaoyouqianhao under salt stress - Guo Xia-Yu (BMC Plant Biology, 2022)
Abstract Background Soil salinization is a threat to food security. China is rich in saline land resources for potential and current utilization. The cultivation and promotion of salt-tolerant rice varieties can greatly improve the utilization of this saline land. The super hybrid rice Chaoyouqianhao (CY1000) is one of the most salt-tolerant rice varieties and is widely used, but the molecular mechanism underlying its salt tolerance is not clear. Results In this study, the characteristics of CY1000 and its parents were evaluated in the field and laboratory. The results showed that aboveground parts of CY1000 were barely influenced by salt stress, while the roots were less affected than those of its parents. A comparative transcriptomic strategy was used to analyze the differences in the response to salt stress among the male and female parents of CY1000 at the seedling stage and the model indica rice 93–11. We found that the salt tolerance of CY1000 was mainly inherited from its male parent R900, and its female parent GX24S showed hardly any salt tolerance. To adapt to salt stress, CY1000 and R900 upregulated the expression of genes associated with soluble component synthesis and cell wall synthesis and other related genes and downregulated the expression of most genes related to growth material acquisition and consumption. In CY1000 and R900, the expression of genes encoding some novel key proteins in the ubiquitination pathway was significantly upregulated. After treatment with MG-132, the salt tolerance of CY1000 and R900 was significantly decreased and was almost the same as that of the wild type after salt stress treatment, indicating that ubiquitination played an important role in the salt tolerance mechanism of CY1000. At the same time, we found that some transcription factors were also involved in the salt stress response, with some transcription factors responding only in hybrid CY1000, suggesting that salt tolerance heterosis might be regulated by transcription factors in rice. Conclusion Our results revealed that the ubiquitination pathway is important for salt tolerance in rice, and several novel candidate genes were identified to reveal a novel salt tolerance regulation network. Additionally, our work will help clarify the mechanism of heterosis in rice. Further exploration of the molecular mechanism underlying the salt tolerance of CY1000 can provide a theoretical basis for breeding new salt-tolerant rice varieties.